FIZIKA FANIDAN MASALALARNI YECHISHDAGI IKKITA YONDASHUV HAQIDA - Alaminov, M.; Utemuratov, T.; Qidirniyazov, A. (SCIENCE and SOCIETY, 2018)
In the article the two approaches of solving the problems in the course of Physics are considered. In the mathematical approach there are used complex mathematical concepts. It is necessary to point out that in solving tasks in Physics there is another approach we can achieve the desired results without the complex mathematical apparatus.
Keywords: the pendulum; spring pendulum; the period of fluctuations; Newton's law